Chemistry - Yurt, Nasuhi (New Jersey : Everest Production, 2008)
Explores chemistry, a branch of physical science, is the study of the composition, properties and behavior of matter.
Executive producer, Adem Kalec.
Host : Laura Wells.
DVD format.
Keywords: Chemistry